Carbon-Coated Alumina Nanochannels-Based Composite: A Conductivity Analysis by Means of Electrochemical Impedance Spectroscopy - Escrig-Murua, J (Elsevier B.V., 2021)
At present, one main technological concernment focuses on the obtaining materials able to act as molecular sensors, which show specific and fast response, high sensitivity, portability and low fabrication cost for monitoring global environmental or medical necessities. Among others, carbon-based composites play a key role in the development of new devices of interest in molecular sensing. In this work, a composite constituted by sputtered carbon as coating of randomly distributed alumina nanochannels is presented. Morphological characterization of this hybrid composite evidences a noticeable high surface area originated in the controlled decoupling of the alumina templates by a low-cost and easy-implementation route. A comparative analysis between results obtained by electrochemical impedance spectroscopy for carbon-coated alumina nanochannels and separated components reveals that the closest value of conductivity to that of carbon nanotubes is achieved by the novel composite. This result hints that the new carbon-nanostructured alumina material could provide competitive alternatives for sensing applications. © 2021 Elsevier B.V.